Shape-controlled bismuth nanoflakes as highly selective catalysts for electrochemical carbon dioxide reduction to formate. (September 2017) - Kim, Sungjoo; Dong, Wan Jae; Gim, Seungo; Sohn, Woonbae; Park, Jae Yong; Yoo, Chul Jong; Jang, Ho Won; Lee, Jong-Lam
Abstract: Nanostructured bismuth (Bi) nanoflakes were designed and directly grown on Cu substrate using a novel pulse electrodeposition method. Compared with conventional bismuth film grown by direct current electrodeposition, Bi nanoflakes have large number of edge and corner sites. As it has been proven by numerical simulation, sharp edge or corner sites of the nanostructures form strong local electric fields, which boost the catalytic activity for the electrochemical reduction of CO2 in aqueous solution. The Bi nanoflakes showed a high HCOO - faradaic efficiency (FE = 79.5%) at low potential of −0.4 VRHE and achieved a maximum FE close to 100% at −0.6 VRHE, meaning that the shape control of Bi electrocatalyst is indeed an efficient way to reduce the electrical power consumption for HCOO - production. Moreover, Bi nanoflakes were stable during 10 h operation in 0.1 M KHCO3 aqueous solution. The results suggest that tailoring the nanostructure is a key in developing a high performance noble-metal-free electrocatalyst for electrochemical CO2 reduction in aqueous solution. Graphical abstract: Bismuth (Bi) nanoflakes were designed using a novel pulse electrodeposition method. Compared with conventional Bi film grown by direct electrodeposition, Bi nanoflakes have a large number of edge and corner sites, which boost the catalytic activity. The novel-metal-free Bi electrocatalyst achieved highly electrochemical CO2 reduction in aqueous solution. Highlights: Bismuth (Bi) nanoflakes were designed and directly grown on Cu substrate using a novel pulse-electrodeposition method. Relationship between the shape and catalytic performance was elucidated. Electrochemical CO2 reduction with high HCOO - production rate was achieved at low potential.